2016
DOI: 10.5604/12314005.1213541
|View full text |Cite
|
Sign up to set email alerts
|

Safety Performance Indicators Assessment for Small Aircraft Airframe Systems

Abstract: Safety performance indicators are the parameters used for monitoring and assessing safety performance. Such factors are determined based on available safety databases, collected on government level (in Poland Civil Aviation Authority) or by aircraft operators. Aircraft system failure during different flight phases can cause an accident or an incident. Polish Civil Aviation Authority between other data bases manages two important ones called: European Coordination Centre for Aviation Incident Reporting Systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The number of events caused by birds was referred to the number of aircraft registered in a given year to objectify the results of comparisons (Balicki W. et al 2016). Coefficient has been added as: (1) where: Nev is the number of events involving birds and Nreg is the number of aircraft registered in the year under consideration.…”
Section: Methodology Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The number of events caused by birds was referred to the number of aircraft registered in a given year to objectify the results of comparisons (Balicki W. et al 2016). Coefficient has been added as: (1) where: Nev is the number of events involving birds and Nreg is the number of aircraft registered in the year under consideration.…”
Section: Methodology Of Analysismentioning
confidence: 99%
“…This type of research was carried out for the first time in our country, on a specially constructed test stand equipped with a pneumatic launcher and measuring apparatus (see Fig. 12) (Balicki at al., 2016). The pneumatic launcher with a 75-m barrel was supplied with compressed air (maximum pressure 0.8 MPa).…”
Section: Tests Of Engine Resistance To Bird Collisionsmentioning
confidence: 99%
“…A methodology was developed to determine the forecast for the following year and to set alert levels for representative types of events, adopting the criterion 2σ. In order to make data analysis more objective, coefficients were introduced relating the number of events to the number of registered aircraft (per 1,000 aircraft) [9][10][11]. It would be more accurate to link the number of incidents to flight time, but there is no relevant data.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists of the Institute of Aviation have done a laborious processing of the data contained in that database analyzing them based on various criteria: 2 aviation occurrence categories (as defined by ICAO), 3 ATA chapters, 4 phases of flight for different airports in Poland, etc. Separately under consideration were aircraft with an MTOM <5700 kg (mainly General Aviation also called as a small aircraft) 5,6,7 and for aircraft with MTOM >5700 kg (Commercial Aviation – large aircraft). It was found that the largest part of the events are those that relate to powerplant, airframe and its systems failures.…”
Section: Introductionmentioning
confidence: 99%